Alinhamento entre as competências fundamentais demandadas pelos programas de trainees de gestão e o ensino de graduação em administração: um estudo de caso na cidade do Rio de Janeiro - Freitas, Julio Cezar Del Rio Chagas de (2006)
The competence theme has become more and more important to employees, employers and young adults looking for their first job. The educational systems, especially the universities, have always tried to prepare individuals who are capable of adapting to new realities, and of acquiring new competences. Therefore these universities formulate their educational programs that aim at developing the student s ability to perform well in the job market. Understanding the alignment between the essential competences demanded by companies in their selection of business administration trainees and what is offered by the graduation courses in Business Administration is the aim of this paper. In this exploratory study, four coordinators of Business administration courses and three managers of trainee programs were interviewed. The research revealed significant evidence of a non-alignment between the essential competences demanded by companies and the educational programs offered by the researched courses